Comparison of Miller and Airtraq laryngoscopes for orotracheal intubation by physicians wearing CBRN protective equipment during infant resuscitation: a randomized crossover simulation study. Issue 1 (December 2016) - Claret, Pierre-Géraud; Asencio, Renaud; Rogier, Damien; Roger, Claire; Fournier, Philippe; Tran, Tu-Anh; Sebbane, Mustapha; Bobbia, Xavier; Emmanuel de La Coussaye, Jean
Abstract Background The purpose of this study was to evaluate the performance of orotracheal intubation with the Miller laryngoscope compared with the Airtraq laryngoscope by emergency and pediatric physicians wearing CBRN-PPE type III on infant manikins with conventional airway. We hypothesized that in this situation, the orotracheal intubation with the Airtraq laryngoscope would be faster and more effective than with the Miller laryngoscope. Methods This was a prospective, randomized, crossover, single-center study who recruited emergency department physicians on a voluntary basis. Each physician performed a total of 20 intubation trials while in CBRN-PPE with the two intubation techniques, Miller and Airtraq. Intubations by each airway device were tested over ten consecutive runs. The order of use of one or the other devices was randomized with a ratio of 1:1. The primary endpoint was overall orotracheal intubation success. Results Fifty-five emergency and pediatric physicians were assessed for eligibility. Forty-one physicians were included in this study and 820 orotracheal intubation attempts were performed. The orotracheal intubation success rate with the Airtraq laryngoscope was higher than with the Miller (99 % vs. 92 %;p -adjusted <.001). The orotracheal intubation and glottis visualization times decreased with the number of attempts (p <.001). The median orotracheal intubation time with the Airtraq laryngoscope was lower than with the Miller laryngoscope (15 s vs. 20 s;p -adjusted <.001). The median glottis visualization time with the Airtraq laryngoscope and with the Miller laryngoscope were not different (6.0 s vs. 7.5 s;p -adjusted =.237). Thirty-four (83 %) physicians preferred the Airtraq laryngoscope versus 6 (15 %) for the Miller (p -adjusted <.001). Discussion For tracheal intubation by physicians wearing CBRN-PPE during infant resuscitation simulation, we showed that the orotracheal intubation success rate with the Airtraq laryngoscope was higher than with the Miller laryngoscope and that orotracheal intubation time with the Airtraq laryngoscope was lower than with the Miller laryngoscope. Conclusions It seems useful to train the physicians in emergency departments in the use of pediatric Airtraq and for the management of CBRN risks.